Kariera jako „własność” jednostki – rozważania teoretyczne nad definicyjnym credo - Cybal-Michalska, Agnieszka (Kultura-Społeczeństwo-Edukacja, 2012)
The narration of this article is focused on showing various ways of capturing the phenomenon of career from a subjective perspective. The subject of an analysis will be the reconstruction of chosen theoretical perspectives, where one emphasizes changes in quality attitude to the career phenomenon and showing the “career making” meaning of people’s activities. The content presented in this article is concentrated on a subjective, personal aspect of capturing a career. In this sense, career is always ascribed to a specific individual, it is their assets and this particular individual attaches importance to the career phenomenon. In this sense, career is the sequence of experiences of a particular individual, linked with the quality of a professional life; this is a unique structure, resulting from autonomous choices.